Unveiling Ideology In The Lyrics Of Wak Uteh Groups “Angin Koncang (High Wind)” : A Systemic Functional Analysis On A Song Lyrics With Tanjungbalai Malay Language - M. Asril Marpaung (PT. Padang Tekno Corp, 2025)
This paper discusses the use of Language Metafunction in a Tanjungbalai Malay language song “Angin Koncang (High Wind)”. This research aims to identify the ideology of the song as portrayed through words and action of the protagonist in this song. This research focused on every single word in the lyric. The study used qualitative and descriptive methods. The data collection was obtained from smule.com. The data was analyzed by using Language Metafunction theory by Halliday’s Ideational, Interpersonal, and Textual Meaning. The results of the research show that three dominant processes of language can be found are Material Process, Relational Process, and Mental Process; with the first mentioned being the dominant one. Also, by analyzing the lyric, it can be concluded that the ideology of the song is to promote an ideology of pragmatic survival and functional relationships